Mesolimbic opioid-dopamine interaction is disrupted in obesity but recovered by weight loss following bariatric surgery - Karlsson Henry K; Tuominen Lauri; Helin Semi; Salminen Pauliina; Nuutila Pirjo; Nummenmaa Lauri (SPRINGERNATURE, 2022)
Obesity is a growing burden to health and the economy worldwide. Obesity is associated with central mu-opioid receptor (MOR) downregulation and disruption of the interaction between MOR and dopamine D-2 receptor (D2R) system in the ventral striatum. Weight loss recovers MOR function, but it remains unknown whether it also recovers aberrant opioid-dopamine interaction. Here we addressed this issue by studying 20 healthy non-obese and 25 morbidly obese women (mean BMI 41) eligible for bariatric surgery. Brain MOR and D2R availability were measured using positron emission tomography (PET) with [C-11]carfentanil and [C-11]raclopride, respectively. Either Roux-en-Y gastric bypass or sleeve gastrectomy was performed on obese subjects according to standard clinical treatment. 21 obese subjects participated in the postoperative PET scanning six months after bariatric surgery. In the control subjects, MOR and D2R availabilities were associated in the ventral striatum (r = .62) and dorsal caudate (r = .61). Preoperatively, the obese subjects had disrupted association in the ventral striatum (r = .12) but the unaltered association in dorsal caudate (r = .43). The association between MOR and D2R availabilities in the ventral striatum was recovered (r = .62) among obese subjects following the surgery-induced weight loss. Bariatric surgery and concomitant weight loss recover the interaction between MOR and D2R in the ventral striatum in the morbidly obese. Consequently, the dysfunctional opioid-dopamine interaction in the ventral striatum is likely associated with an obese phenotype and may mediate excessive energy uptake. Striatal opioid-dopamine interaction provides a feasible target for pharmacological and behavioral interventions for treating obesity.